THE POLITICS OF BELONGING: PLUNDERING THE LOCAL, CLAIMING THE GLOBAL - Agus Indiyanto (Humaniora, 2012)
The 'global' and 'local' are often conceptually perceived as an opposite and obliterate. Due to the intensive process of globalization, many people imagined about the vanishing process of locality. The intensive migration towards cities and the internalization of new dies into the local community through the telecommunication infrastructures would directly affect the existence of localities. All of this process leads to the alienation of local community to their values and cultures. Same scholars demonstrate that the globalization also initiate the new globalized cultures which clearly shows their local roots. Migration to the cities, however, did not simultaneously push people away from their connections with the village of origin. Some studies showed that in many societies there were growing tendencies of migrants involved actively sponsor the local rituals at their home village to regain new status. This phenomenon indicate that the 'global' and the 'local' are not always in an opposite position, rather than complementary. Accordingly, the intensive globalization did not eradicate localities, but in many cases revitalize it although in different forms and values.